Experience using low doses of calcineurin inhibitors in the treatment of refractory lupus nephritis - César Augusto Restrepo Valencia; Consuelo Vélez Álvarez (Revista Colombiana de Nefrología, 2014)
Objective: To evaluate the effectiveness of calcineurin ciclosporin and tacrolimus inhibitors to induce remission in patients with refractory lupus nephritis.